Fake News as a Democratic Anathema: A Comparative Study between India and Indonesia - Ishita Sharma; Mansi Aggarwal (Faculty of Law, Hasanuddin University, 2019)
The undeniably mind boggling media landscape has tossed fresh difficulties to an unsettled environment of media policy and that is why the market is denuded with fake news: scattered through social media intermediaries. Absence of effective laws for the same, have worsened the situation in recent past. Through this paper the researchers have tried to inspect how the propagation of fake news has upset the public sphere and potential arrangements that can be executed to check the plague of fake news in context of India and Indonesia, the prime democracies. There is boisterous discussion on fake news being utilized to create a rosy impression of the politicians in the minds of citizens. Therefore, the researcher shall also cover this aspect by analyzing how fake news has affected elections and how it was used as a tool of mass deception respectively. Finally, it attempts to analyze various strategic initiatives taken by both the nations, and the potential measures which could be adopted to limit the progression of fake news.